1998
DOI: 10.1006/dbio.1998.8865
|View full text |Cite
|
Sign up to set email alerts
|

Growth Promoting Activity of Oocytes on Granulosa Cells Is Decreased upon Meiotic Maturation

Abstract: An increasing body of evidence indicates that the oocyte plays an active role in the control of ovarian follicle development in mammals. In the present study, we have examined the role of oocytes in regulating granulosa cell proliferation. Rat and bovine oocytes cocultured with rat granulosa cells stimulated granulosa cell DNA synthesis and DNA content in the cultures. FSH or cAMP further amplified this effect. Poor-quality oocytes showed a marked decrease in their stimulatory effect. Stimulation of DNA synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 44 publications
3
23
0
Order By: Relevance
“…These findings are consistent with their known roles on ovarian follicular development in vivo (Juengel & McNatty 2005). Collectively, the aforementioned results are consistent with previous reports showing dose-related effects of mouse, rat or bovine oocytes on 3 H-thymidine incorporation by rodent GC (Vanderhyden et al 1992, Lanuza et al 1998, Otsuka & Shimasaki 2002, Gilchrist et al 2004. Despite a dose response effect of rat oocyte numbers on 3 H-thymidine incorporation by rat GC, 3 H-thymidine incorporation in rat DO-GC co-incubations was only reduced after blocking the action of GDF9 and not of BMP15.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are consistent with their known roles on ovarian follicular development in vivo (Juengel & McNatty 2005). Collectively, the aforementioned results are consistent with previous reports showing dose-related effects of mouse, rat or bovine oocytes on 3 H-thymidine incorporation by rodent GC (Vanderhyden et al 1992, Lanuza et al 1998, Otsuka & Shimasaki 2002, Gilchrist et al 2004. Despite a dose response effect of rat oocyte numbers on 3 H-thymidine incorporation by rat GC, 3 H-thymidine incorporation in rat DO-GC co-incubations was only reduced after blocking the action of GDF9 and not of BMP15.…”
Section: Discussionsupporting
confidence: 93%
“…However, it is known that when the health of follicles based on GC criteria is assessed, BMP15 and GDF9 mRNA are significantly lower in atretic compared with healthy follicles . Moreover, Lanuza et al (1998) have reported that poor quality bovine oocytes are less effective than good quality oocytes in stimulating 3 H-thymidine uptake by rat GC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the oocyte regulates a broad range of granulosa cell functions through the release of paracrine signals. Germ cells stimulate granulosa cell proliferation and differentiation [45][46][47][48], modulates steroidogenesis [49], expression of the c-kit ligand [50], LH receptor (LHR [51]), hyaluronic acid (HA) synthesis [52] and urokinasetype plasminogen activator (uPA [53]). As antral follicle is formed, a gradient of oocyte-secreted factors directs the specialization of the surrounding granulosa cells, referred to as cumulus cells, in a s p e c i f i c p h e n o t y p e , i n o r d e r t o c r e a t e a microenvironment capable to better respond to the oocyte requirements.…”
Section: An Overview Of Oocyte and Follicle Developmentmentioning
confidence: 99%
“…In addition to the communication through gap junctions, both granulosa cells and oocytes produce paracrine factors [19,20], which are important in the regulation of oocyte growth and follicular development. For example, growth differentiation factor-9, which is produced by oocytes, promotes granulosa cell proliferation [21][22][23], and regulates granulosa cell differentiation [24][25][26][27][28]. Moreover, oocytes seem to promote the formation of follicular antrum [29,30], so that there is a bidirectional regulatory loop between the oocytes and their companion granulosa cells [31,32].…”
mentioning
confidence: 99%